Períodos de convivência das plantas daninhas no feijoeiro inoculado com Rhizobium tropici ou com adubação nitrogenada - Franciscon, Hugo (2017)
Two researches were conducted, the first in order to solve a methodological problem and the second aimed to investigate the effects of inoculation and nitrogen fertilization on the period prior to interference (PPI) in bean crop. First research: In the literature there are different methodologies for the establishment of interference periods; however, none of them combined accuracy, practicality and the inclusion of economic factors. Therefore, a research was carried out aiming the development of a new methodology that includes economic factors, accuracy and practicality; proving their applicability and accuracy in the data obtained from the literature and test its practicality based on hypothetical data. The integral method was obtained as a result, which was tested on interference periods data from the literature and compared with other methods, proving to be efficient; however, it fell short in practicality. To make the method more practical, a equations bank was elaborated, which was tested by means of hypothetical data; the equations present in the bank, proved to be accurate and, thus, made it possible to make the integral method, besides being precise, practical. Therefore, it was concluded that the integral method combined the practicality, precision and the use of economic factors in the determination of interference periods, achieving the established objectives. Second research: The objective was to verify if the substitution of the broadcast nitrogen fertilization by the inoculation with R. tropici can increase the bean crop tolerance to the weed interference and, thus, to extend its PPI. Two experiments of coexistence periods were installed during the seasons of 2014 and 2015. The experimental design was a randomized block design, with 4 replications, in a 2x10 factorial scheme, 2 handlings and 10 coexistence periods. The periods, in days after emergence (DAE), were 0 (control), 14, 21, 28, 35, 42, 49, 56, 63 and 90 (until harvest). At the end of each period the floristic survey was performed, calculating the density and dry mass of each weed species. A curve of accumulation of dry mass of the aerial part of the crop was also elaborated and its phenological stages determined. At harvest was performed to count the population of bean plants and determined the thousand grain weight and productivity of the culture. The PPI was determined by the integral method, the criterion used to determine the tolerated loss was the economic criterion of the WEEPEL. The substitution of broadcast nitrogen fertilization by inoculation with Rhizobium tropici did not increase the crop ability to compete with weeds and did not lengthen the PPI, which was provided by the use of broadcast nitrogen fertilization. The PPI for the bean under handling without broadcast nitrogen fertilization and with inoculation (without N) was between 17.80 and 49.51 DAE in mean of seasons; While when under handlinf with broadcast nitrogen fertilization and without inoculation the PPI was between 26.38 and 57.06 DAE, in mean of seasons.